Relationship between neurocognitive functioning and episode recurrences in bipolar disorder - Martino, Diego Javier (2012)
Background: The relationship between neurocognitive impairments and clinical course in bipolar disorder (BD) is inconclusive. The aim of this study was to compare time to recurrence between patients with and without clinically significant cognitive impairments. Methods: Seventy euthymic patients with BD were included. Based on baseline neurocognitive performance patients were divided as those with (n=49) and without (n=21) clinically significant cognitive impairments. Both groups of patients were prospectivelly assessed by a modified life chart method during a mean of 16.3 months. Results: Patients with some cognitive domain compromised had an increased risk of suffering any recurrence (HR: 3.13; CI95%: 1.64-5.96), hypo/mainc episodes (HR2.42; CI95%:1.13-5.19), or depressive episodes (HR; 3.84; CI95%: 1.66-8.84) compared with those patients without clinically significant cognitive impairments. These associations remained significant after adjust for several potential counfounders such as number of previous episodes, time since last episode, clinical subtype of BD, exposure to antipsychotics, and subclinical symptoms. Limitations: We clasified patients as with or without clinically significant cognitive impairments, although deficits in different cognitive domains may not be equivalent in terms of risk of recurrence. Conclusions: The results did not support the hypothesis that the experience of successive episodes is related to a progressive neurocognitive decline. Contrarily, cognitive impairments could be the cause more than the consequence of poorer clinical course. Alternativelly, a specific subgroup of patients with clinically significant cognitive impairments and a progressive illness in terms of counts of recurrences, and shortening of wellness intervals might explain the association showed in this study.